2016
DOI: 10.3168/jds.2015-10130
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of progesterone on fertility of dairy and beef cows

Abstract: The role of progesterone in maintaining pregnancy is well known in the bovine. Subtle differences exist between dairy and beef cows because of differing concentrations of progesterone during recrudescence of postpartum estrous cycles, rate of follicular growth and maturation, proportions of 2- and 3-follicular wave cycles, and other effects on pregnancy outcomes per artificial insemination (P/AI). Because proportions of anovulatory cows before the onset of the artificial insemination (AI) period are greater an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…Differences in progesterone concentrations across studies are likely to be due to the use of different assays (e.g. chemiluminescence in this study versus radioimmunoassay in others), differences in the proportion of cows in post‐partum anoestrus at the start of treatment programs and differences between beef and dairy cows . Although P4 a cutoff of <1 ng/mL has been used in other studies to classify cows as having undergone luteolysis, in our data, there appears to be a distinct cut‐off point of 3 ng/mL at the time of AI in the OV group (Figure ) and a cut‐off point of 2 ng/mL at the time of AI in the MO group (Figure ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Differences in progesterone concentrations across studies are likely to be due to the use of different assays (e.g. chemiluminescence in this study versus radioimmunoassay in others), differences in the proportion of cows in post‐partum anoestrus at the start of treatment programs and differences between beef and dairy cows . Although P4 a cutoff of <1 ng/mL has been used in other studies to classify cows as having undergone luteolysis, in our data, there appears to be a distinct cut‐off point of 3 ng/mL at the time of AI in the OV group (Figure ) and a cut‐off point of 2 ng/mL at the time of AI in the MO group (Figure ).…”
Section: Discussionmentioning
confidence: 65%
“…Since the rate of luteolysis increases with the age of the CL, a second dose of PGF 24 h after the first would be expected to coincide with the time of responsiveness of the CL to PGF administration of PGF . In this study, concentrations of progesterone at the time of FTAI were higher than that recorded in other studies where cows were sampled 48–72 h after administration of PGF using GnRH‐based treatment protocols . Differences in progesterone concentrations across studies are likely to be due to the use of different assays (e.g.…”
Section: Discussionmentioning
confidence: 69%
“…According to previous studies, several factors may affect the conception rates of animals supplemented with P4, and this complexity can be noted in the experiments of Larson et al (2009), who found positive effects on fertility, when dairy cows were supplemented with a progesterone intravaginal device; however, these authors found no improvement in beef cows that received the same treatment, at the same time, which suggested that there was a difference in response to treatment according to the type of animal that was treated (beef or dairy). Stevenson and Lamb (2016) proposed that physiological differences, including the circulating concentrations of progesterone and responses to supplemental progesterone, affected by the genotype and nutritional management of the animals, could account for the variation.…”
Section: Resultsmentioning
confidence: 99%
“…bras., Brasília, v.53, n.1, p.105-112, Jan. 2018 DOI: 10.1590/S0100-204X2018000100012 preimplantation phase, and provided an adequate uterine environment for conception (Davoodi et al, 2016). Furthermore, adequate concentrations of E2 during the final follicular growth were positively correlated with the preovulatory follicle diameter and luteal function, which facilitated the establishment and maintenance of pregnancy (Bridges et al, 2012;Stevenson & Lamb, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding endometrial receptivity, experiments performed in Nellore cows and Simmental heifers 19,21,22 , after estrus synchronization, have unveiled important differences in the endometrial transcriptome at day 6 or 7 of animals that become pregnant after AI or embryo transfer (ET), respectively, compared to the non-pregnant ones. However, disparities in embryo survival between heifers and lactating cows 2 , the different effects of progesterone on the fertility of dairy and beef cows 23 and the variations in hormonal concentration and uterine thickness between induced or natural estrus 17 , indicate the need of further studies for a better comprehension of the mechanisms controlling endometrial receptivity.…”
Section: Introductionmentioning
confidence: 99%